2022
DOI: 10.1186/s13046-022-02258-9
|View full text |Cite
|
Sign up to set email alerts
|

HPV-mediated regulation of SMAD4 modulates the DNA damage response in head and neck cancer

Abstract: Background Head and Neck cancer (HNC) is a fatal malignancy with poor prognosis. Human Papillomavirus (HPV) infection is becoming the prominent cause of HNC in the western world, and studying the molecular mechanisms underlying its action in cancers is key towards targeted therapy. To replicate, HPV regulates the host DNA damage repair (DDR) pathway. SMAD4 is also involved in the regulation of the DDR machinery and likely plays important role in maintaining cell viability upon genotoxic stress.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…Many previous studies have provided the same point, but the exact mechanism of action remains to be elucidated. 51,52 The data showed a positive association between may also regulate macrophage infiltration. Tumor-associated macrophages (TAMs) can be divided into M1 and M2 subtypes; the former tends to exert antitumor activity, while the latter tends to promote tumor development.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Many previous studies have provided the same point, but the exact mechanism of action remains to be elucidated. 51,52 The data showed a positive association between may also regulate macrophage infiltration. Tumor-associated macrophages (TAMs) can be divided into M1 and M2 subtypes; the former tends to exert antitumor activity, while the latter tends to promote tumor development.…”
Section: Discussionmentioning
confidence: 84%
“…Among them, the rate of high MYO1B expression was higher in the HPV infection‐negative group, and the rate of low MYO1B expression was higher in the HPV infection‐positive group. Many previous studies have provided the same point, but the exact mechanism of action remains to be elucidated 51,52 …”
Section: Discussionmentioning
confidence: 92%
“…SMAD4 functions at the G1/S checkpoint and causes cells to stall in G1 phase, resulting in cell-cycle arrest (21). The DNA damage and genomic instability caused by SMAD4-deletion results in poor survival and drug resistance in patients with squamous cell carcinoma of the head and neck (22)(23)(24). Accumulating evidence has revealed that patients with loss of SMAD4 have more chance to develop metastatic relapse (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…For cell-growth studies, the University of Michigan Squamous Cell Carcinoma-23 (UM-SCC-23, target cells) [ 55 ] were maintained as we previously reported [ 56 ] and seeded at 25 × 10 4 cell/well on iCelligence E-plate L8 (ACEA Biosciences) for 2 h before the addition of effectors. Buffy-coats from healthy donors were obtained from the ASL2 Lanciano-Vasto-Chieti (Abruzzo, Italy) transfusion center after informed consent.…”
Section: Methodsmentioning
confidence: 99%